Sri Lanka : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper focuses on the fiscal position of Sri Lanka. The standard analysis shows that, prior to the adjustment announced in the 2002 budget, fiscal policy was clearly unsustainable, leading to a rising debt-to-GDP ratio. The paper looks at external debt and complements the analysis of the public debt dynamics. The baseline scenario shows that debt ratios decline significantly in the medium term, as a result of strong growth founded on renewed peace and political stability, far-reaching structural reforms, and stable macroeconomic conditions.